ANALIS PREDIKSI PENERIMAAN LEVEL SINYAL PADA DAERAH SUB URBAN TERHADAP UNJUK KERJA JARINGAN GSM - Muhammad Mudjiono . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Sub-urban area is a suburban area (rural) with some of the barriers of trees, houses and buildings that are not too high under 5 level. Some of the causes of interruption of the call is limited channel reception level talks and the problem of RF signals (radio frequency) where the quality of the signal level is strongly influenced by local conditions damping propagation. The study was conducted in village siduk, districtsnanga tayap, north kayong district, Problems GSM network performance can be seen from the monitoring of traffic through NetAct software by using parameter-parameter above as: SDCCH Blocking, SDCCH Drop, Loss RF SDCCH, TCH Blocking, TCH Drop, and TCH RF Loss. Then do the calculation Prediction Reception signal level using Okomura-Hatta. Manual calculation results in BTS North Kayong siduk shows that the BTS antenna sector 1 with a power 27 W is obtained within a range of 3.2 km with a reception signal level -80 dBm, while the range desired by PT. Telkomsel is 3.5 Km, then power must be increased to 34.62 W. In sector 2, the transmit power of 27 W, within a range of 3.2 km, with the reception signal level -80 dBm, the desired range of 3.8 Km, power must be increased to 35.80 W. in the third sector, the transmit power of 26 W, within a range of 3.1 km, with the reception signal level -80 dBm, the desired range 3.5 Km, power should rise to 34.26 W. from the results of calculations can be concluded that the performance of the BTS antennas siduk north Kayong less than the maximum because of the decreasing transmission power due to the loss of damping propagation in sub urban Reviewed sector antenna 1 is (2 dBm), sector 2 is (3 dBm), sector 3 is (3 dBm). But in general is still quite good. Key word : Sub- urban , NETACT , Traffic , Okomura – Hatta.